2013
DOI: 10.7314/apjcp.2013.14.1.429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Tumor Angiogenesis and Perfusion Imaging Using Multi-slice Spiral Computed Tomography for Breast Cancer

Abstract: Objectives: To explore the correlation between multi-slice spiral CT (MSCT) perfusion parameters and the expression of vascular endothelial growth factor (VEGF) as well as matrix metalloproteinase-2 (MMP-2) in breast cancer. Methods: Forty five breast cancer patients and 16 patients with benign breast tumor, both confirmed by pathology examination, were enrolled. All underwent MSCT perfusion imaging to obtain perfusion maps and data for parameters including blood flow (BF), blood volume (BV) and permeability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…We also noticed higher plasma levels for VEGF and TIMP-1 in BC group in comparison to the group with benign lesions (statistical significance). Similar data were observed in our previous study 26 and in the paper by Xu et al, 58 though these authors compared only 45 patients with BC to 16 patients with benign lesions.…”
Section: Discussionsupporting
confidence: 90%
“…We also noticed higher plasma levels for VEGF and TIMP-1 in BC group in comparison to the group with benign lesions (statistical significance). Similar data were observed in our previous study 26 and in the paper by Xu et al, 58 though these authors compared only 45 patients with BC to 16 patients with benign lesions.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that 4-HNE increased angiogenesis and the levels of expression of VEGF of breast cancer cell. Although, the overexpression of VEGF in breast cancer can reflect the potential of angiogenesis (including blood flow, blood volume and permeability surface) in the tumor tissue (Xu et al, 2013), further research is required to determine whether the levels of 4-HNE was correlated with VEGF expression and angiogenesis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The molybdenum target X-ray is the most common means to screen and diagnose breast cancers and can identify calcified lesions with high sensibility (2). MSCT is mainly used for judging whether the thoracic lymph nodes are affected, which influences the surgical procedure planning (3). MRI, in turn, can evaluate the tumor size, the tumor-infiltrating range and the situation of peripheral lesions very accurately and is more sensitive than an ultrasound inspection, which has significant auxiliary value in the application of breast-conserving surgery (4).…”
Section: Introductionmentioning
confidence: 99%